Loneliness among dementia caregivers: evaluation of the psychometric properties and cutoff score of the Three-item UCLA Loneliness Scale - Ali, Amira Mohammed; Al-Dossary, Saeed A.; Laranjeira, Carlos; Selim, Abeer; Hallit, Souheil; Alkhamees, Abdulmajeed A.; Aljubilah, Aljawharah Fahad; Aljaberi, Musheer A.; Alzeiby, Ebtesam Abdullah; Pakai, Annamaria; Khatatbeh, Haitham (Frontiers in Psychiatry, 2025)
IntroductionDementia is a chronic progressive syndrome, with an entire loss of function in the late stages. The care of this demanding condition is primarily provided by family members, who often suffer from chronic burnout, distress, and loneliness. This instrumental study aimed to examine the factor structure, reliability, convergent validity, criterion validity, and cutoff scores of a short loneliness measure: the Three-Item version of the University of California, Los Angeles, Loneliness Scale (UCLALS3) in a convenience sample of dementia family caregivers (N = 571, mean age = 53 ±12 years, 81.6% females).MethodsExploratory and confirmatory factor analyses were used to examine the structure of the UCLALS3 while receiver-operating characteristic (ROC) curve, including caregiving burden and emotional distress as outcomes, was used to examine its cutoff.ResultsOne factor accounted for 79.0% of the variance in the UCLALS3; it was perfectly invariant across genders but variant at the metric level across countries. The scale had adequate internal consistency (alpha = 0.87), high item-total correlations (0.69 – 0.79), reduced alpha if item deleted (0.77 – 0.86), and strong positive correlations with caregiving burden and psychological distress scores (r = 0.57 & 0.74, p values = 0.01). Percentile scores and the ROC curve suggested two cutoffs (≥6 and ≥6.5), which classified 59.3 and 59.4% of the participants as having higher levels of loneliness—comparable to global levels of loneliness among informal caregivers. The Mann-Whitney test revealed significantly high levels of caregiving burden and distress in caregivers scoring ≥6.5 on the UCLALS3.ConclusionThe UCLALS3 is a valid short scale; its cutoff ≥6.5 may flag major clinically relevant symptoms in dementia caregivers, highlighting the need for tailored interventions that boost caregivers’ individual perception of social relationships. More investigations are needed to confirm UCLALS3 invariance across countries.